CHILDREN’S UPBRINGING AND THE ROLE OF THE TEACHER IN THE WORKS OF THE JADIDS (Лучшие интеллектуальные исследования, 2025)
Abstract: This article examines the perspectives of the Jadid reformers on children’s upbringing and the pivotal role of teachers in shaping future generations. The Jadids, who emerged as progressive intellectuals in Central Asia during the late 19th and early 20th centuries, emphasized modern education as a cornerstone for social reform and cultural renewal. Through an analysis of key Jadid literary and pedagogical works, this paper explores how children’s moral, intellectual, and physical development was prioritized, and how teachers were portrayed as essential agents of enlightenment, guidance, and national progress. The study highlights the Jadids’ advocacy for a new pedagogical approach that combines traditional values with modern educational methods.